Desert ants avoid ambush predator pits depending on position, visual landmarks and trapped nestmates - Adi Bar; Eden Raveh-Pal; Aziz Subach; Susanne Foitzik; Inon Scharf (Royal Society Open Science)
Central-place foragers face high predation risk when repeatedly using routes near their nest, as predators can learn to ambush them there. We investigated the factors influencing the likelihood of desert ant foragers falling into pitfall traps, simulating common predators such as antlions or spiders. We varied the spatial configuration of the pitfall traps, the presence of trapped nestmates and the availability of visual landmarks to study the workers’ susceptibility to falling into pits and their foraging success. Our results showed that a zigzag configuration of pits led to the fewest workers reaching the food reward, compared with straight-line and right-angled-triangle configurations. Over successive runs, workers became more efficient, with fewer falls into pits and faster food discovery, suggesting they either learned the locations of the pits or became more cautious. In any case, the ants learned about important landscape features close to their nest and the best way of navigating around it. Additionally, we examined the impact of trapped nestmates and visual landmarks. We found that pits marked with visual landmarks resulted in fewer falls. However, pits containing trapped nestmates attracted more ants, impaired food discovery and increased falling rates into pits, thereby imposing a twofold cost on ant foragers.